2021
DOI: 10.3389/fmed.2021.630160
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplantation Cyclophosphamide, Tacrolimus and Low-Dose ATG as GVHD Prophylaxis for Allogeneic Peripheral Stem Cell Transplantation for Adult Patients With Lymphoid Malignancies: A Single Arm Phase II Study

Abstract: The PT-Cy was considered as one of the mainstay protocol for graft verus host disease (GVHD) prophylaxis. Recent study demonstrated that PT-Cy combined with other immunosuppressants could further reduce the incidence of GVHD and improve the GVHD and relapse free survival (GRFS). In this prospective phase II study, we evaluated the effect of a new GVHD prophylaxis consist of PT-Cy combined with tacrolimus and low dose anti-thymoglobulin (ATG). A total of 23 patients were enrolled including 20 patients with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In addition, the combination of low‐dose pretransplant ATG (5 mg/kg) and PTCy (50 mg/kg on day +3) in the haplo‐PBSCT setting reported by Xu et al showed that cumulative incidence of grade II–IV aGVHD was 17.0% and of grade III–IV aGVHD, 3.2% 21 . In addition, the study reported by Jiang et al showed that PTCy plus low‐dose post‐transplant ATG (2.5 mg/kg) was promising in preventing GVHD in the setting of PBSCT in matched and mismatched transplants 29 . Furthermore, some studies have reported the outcomes of the combination of PTCy and low‐dose ATG in matched and mismatched transplants with encouraging results 18,30 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the combination of low‐dose pretransplant ATG (5 mg/kg) and PTCy (50 mg/kg on day +3) in the haplo‐PBSCT setting reported by Xu et al showed that cumulative incidence of grade II–IV aGVHD was 17.0% and of grade III–IV aGVHD, 3.2% 21 . In addition, the study reported by Jiang et al showed that PTCy plus low‐dose post‐transplant ATG (2.5 mg/kg) was promising in preventing GVHD in the setting of PBSCT in matched and mismatched transplants 29 . Furthermore, some studies have reported the outcomes of the combination of PTCy and low‐dose ATG in matched and mismatched transplants with encouraging results 18,30 .…”
Section: Discussionmentioning
confidence: 98%
“…21 In addition, the study reported by Jiang et al showed that PTCy plus low-dose post-transplant ATG (2.5 mg/kg) was promising in preventing GVHD in the setting of PBSCT in matched and mismatched transplants. 29 Furthermore, some studies have reported the outcomes of the combination of PTCy and low-dose ATG in matched and mismatched transplants with encouraging results. 18,30 Compared to these studies, our reduced-dose PTCy/ATG regimen showed outstanding aGVHD prophylaxis in the setting of haplo-PBSCT.…”
Section: Discussionmentioning
confidence: 99%
“…This work was based on their previous phase II study using PTCy-cyclosporine (CsA) undergoing allogeneic HSCT with peripheral blood stem cell and myeloablative conditioning. Since the incidence of acute GVHD remained high in a haploidentical setting, they replaced CsA with tacrolimus and added a single low dose of ATG after neutrophil engraftment ( 5 ). They observed a low incidence of grade II-IV aGVHD, no cases of grade III-IV aGVHD at day 100 and no cases of steroid-resistant aGVHD.…”
mentioning
confidence: 99%